Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis